2018
DOI: 10.23876/j.krcp.2018.37.2.148
|View full text |Cite
|
Sign up to set email alerts
|

Obesity may be erythropoietin dose-saving in hemodialysis patients

Abstract: BackgroundIn dialysis patients, the obesity-survival paradox still requires an explanation. Anemia and high doses of erythropoiesis-stimulating agents (ESAs) are associated with worse outcomes in the hemodialysis (HD) population. In the present study, we explored the relation between obesity and anemia control in a sample of maintenance HD patients in Egypt.MethodsThis multicenter observational study included 733 patients on maintenance HD from 9 hemodialysis centers in Egypt. Clinical and laboratory data as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Interestingly, the present study [ 1 ] had relatively low ESA doses or ERIs in both non-obese and obese patients (median ESA dose of 6,000 vs. 4,000 U/week; median ERI of 8.0 vs. 4.3) compared to similar studies [ 3 , 4 ]. This seems to be related to the healthier characteristics of patients in this study (younger, less diabetic, and less hypertensive), although the authors showed no detailed information on the comorbidities.…”
mentioning
confidence: 52%
See 3 more Smart Citations
“…Interestingly, the present study [ 1 ] had relatively low ESA doses or ERIs in both non-obese and obese patients (median ESA dose of 6,000 vs. 4,000 U/week; median ERI of 8.0 vs. 4.3) compared to similar studies [ 3 , 4 ]. This seems to be related to the healthier characteristics of patients in this study (younger, less diabetic, and less hypertensive), although the authors showed no detailed information on the comorbidities.…”
mentioning
confidence: 52%
“…I read with interest the article by El-Kannishy et al [ 1 ], in which fewer erythropoietin doses were required to achieve anemia control in obese hemodialysis (HD) patients in a multicenter observation study from Egypt. Given these results, I doubt if obesity, expressed as body mass index (BMI) > 30 kg/m 2 , by itself is an independent factor for determining dosage of erythropoietin-stimulating agents (ESAs).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Whether such a mechanism would result in pregnant women benefiting from obesity, in terms of erythropoiesis maintenance, is an hypothesis worth exploring. Such obesity-associated advantages have recently been reported in people who undergo hemodialysis [23].…”
Section: Discussionmentioning
confidence: 87%